United Republic of Tanzania : Sixth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility and Request for a Three-Year Policy Support Instrument; Staff Report; Staff Supplement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Tanzania. (IMF Staff Country Reports; Country Report, 2007)
This paper discusses key findings of the Sixth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility (PRGF) for Tanzania. Economic growth, inflation, and the external position have evolved in a manner consistent with program objectives, and the program has remained broadly on track. All end-March and end-June 2006 quantitative targets were met, as were structural reforms, with the exception of delays in the energy and pension sectors. The PRGF was extended through end-2006 to permit a fuller articulation of the authorities' policy framework, mainly in energy.